PENYAMPAIAN EDUKASI DAN PENANGANAN KASUS KEGAWATDARURATAN DI KLINIK ASTER - Nissa, Damar Aulia; Anggraeni, Rina Dwi; Atikah, Euis; Putri, Aura; Sarah, Unita (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
An obstetric emergency is an emergency for mothers during pregnancy, childbirth, and postpartum. In obstetric emergencies not treated immediately, this can lead to the death of the mother and fetus. The clinical symptoms of obstetric emergencies are very difficult to recognize, so the knowledge, thinking, analytical skills and experience of midwives as helpers are very important. In health service institutions, midwives are one of the health workers who have important competency standards as a characteristic of professional quality standards in their work. Midwives provide services throughout the mother's life cycle and treat obstetric emergencies, this is inseparable from the knowledge and attitude of midwives towards referrals. Obstetric emergency referral is a timely referral. Successful timely referrals are supported by conditions that can prevent the occurrence of four delays (4T) in the management of obstetric emergencies. A good referral system requires health workers, especially midwives, to be at the forefront of emergency obstetric services. Knowledge and attitude are very important for medical personnel, especially midwives. These advanced skills shape the worker's abilities. This is an initiative to accelerate the reduction of maternal mortality rates in obstetric emergencies. The data analysis in this study was used the SPSS 20 statistical processing program and the test used was the Chi-Square test